Electronic and thermoelectric properties of Zn and Se double substituted tetrahedrite. Issue 45 (8th November 2018) - Tippireddy, Sahil; Chetty, Raju; Raut, Krushna Kumari; Naik, Mit H.; Mukharjee, Prashanta K.; Jain, Manish; Nath, R.; Wojciechowski, Krzysztof; Mallik, Ramesh Chandra
Abstract : The influence of Zn and Se double substitution on the electronic and thermoelectric properties of tetrahedrite is investigated in this study. Abstract : The influence of Zn and Se double substitution on the electronic and thermoelectric properties of tetrahedrite was investigated in this study. The samples Cu11 Zn1 Sb4 S13− x Se x ( x = 0.25, 0.5, 0.75, 1, and 2) were prepared via solid state synthesis followed by field assisted sintering. The density functional theory (DFT) results showed that Se substitution introduces additional bands near the Fermi level ( E F ), with lower effective mass compared to Zn (only) substituted sample Cu11 Zn1 Sb4 S13 . Consequently, the electrical resistivity decreased with the increase in Se content which is attributed to the enhanced charge carrier mobility caused by the more dispersive Se states as indicated by DFT results. But the Seebeck coefficient was invariant with x, due to the enhancement of the density of states (DOS) at E F . The overall effect was an increase in power factor of the Cu11 Zn1 Sb4 S13− x Se x samples compared to Cu11 Zn1 Sb4 S13 . The Zn 2+ substitution at the Cu 1+ tetrahedral site resulted in a decrease of the carrier thermal conductivity due to the decrease in charge carrier concentration. Whereas Se substitution resulted in the decrease of lattice thermal conductivity due to additional phonon scattering caused by the S–Se mass difference. Simultaneous optimization of the power factor and thermal conductivity could thus be achieved via double substitution at Cu and S sites. A maximum thermoelectric figure of merit ( zT ) of 0.86 at 673 K was exhibited by the Cu11 Zn1 Sb4 S12.75 Se0.25 sample due to its relatively high power factor among the samples (0.9 mW m −1 K −2 at 673 K) coupled with very low total thermal conductivity (0.67 W m −1 K −1 at 673 K).